Speech Input as an Alternative Mode to Perform Multi-touch Gestures - Nor Hidayah Hussain; Tengku Siti Meriam Tengku Wook; Siti Fadzilah Mat Noor; Hazura Mohamed (Universitas Ahmad Dahlan, 2018)
Speech is fundamental and the most dominant form of communication. Speech input may facilitate natural interaction between humans and computers. For children, this input mode supports their interaction with application systems. This study addresses speech input as an alternative mode in order to improve multi-touch gesture interactions. Previous studies show that children difficult to perform multi-touch gestures successfully. In fact, multi-touch is parts of basic core gestures that have been adapted to most of the learning applications. This study uses the Wizard-of-Oz method and posts interview, involving nine preschool children between ages of four to six years old. Results of the study show children’s interactional ability using speech input towards systems and positive feedback received from them regarding the prototype of the systems. The findings from this study highlight the opportunities and challenges in using speech input to increase the success of children’s interaction with multi-touch gestures.